Th2 CD4+ T Cells Are Necessary and Sufficient for Schistosoma‐Pulmonary Hypertension. Issue 15 (6th August 2019) - Kumar, Rahul; Mickael, Claudia; Kassa, Biruk; Sanders, Linda; Koyanagi, Dan; Hernandez‐Saavedra, Daniel; Freeman, Scott; Morales‐Cano, Daniel; Cogolludo, Angel; McKee, Amy S.; Fontenot, Andrew P.; Butrous, Ghazwan; et al.
Abstract : Background: Inflammation underlies many forms of pulmonary hypertension (PH), including that resulting from Schistosoma infection, a major cause of PH worldwide. Schistosomiasis‐associated PH is proximately triggered by embolization of parasite eggs into the lungs, resulting in localized type 2 inflammation. However, the role of CD4 + T cells in this disease is not well defined. Methods and Results: We used a mouse model of schistosomiasis‐associated PH, induced by intraperitoneal egg sensitization followed by intravenous egg challenge, with outcomes including right ventricle systolic pressure measured by cardiac catheterization, and cell density and phenotype assessed by flow cytometry. We identified that embolization of Schistosoma eggs into lungs of egg‐sensitized mice increased the perivascular density of T‐helper 2 (Th2) CD4 + T cells by recruitment of cells from the circulation and triggered type 2 inflammation. Parabiosis confirmed that egg embolization is required for localized type 2 immunity. We found Th2 CD4 + T cells were necessary for Schistosoma ‐induced PH, given that deletion of CD4 + T cells or inhibiting their Th2 function protected against type 2 inflammation and PH following Schistosoma exposure. We also observed that adoptive transfer of Schistosoma ‐sensitized CD4 + Th2 cells was sufficient to drive type 2 inflammation and PH. Conclusions: Th2 CD4 + T cells are a necessary and sufficient component for the type 2 inflammation‐induced PH following Schistosoma exposure.